Design of double-component metal–organic framework air filters with PM2.5 capture, gas adsorption and antibacterial capacities. (1st January 2019) - Ma, Shanshan; Zhang, Meiyun; Nie, Jingyi; Tan, Jiaojun; Yang, Bin; Song, Shunxi
Graphical abstract: Highlights: Novel Ag-MOFs@CNF@ZIF-8 cellulose-based air filters were designed and fabricated. The Ag-MOFs were employed to endow filters with excellent antibacterial activity. The ZIF-8 nanocrystals were used to endow filters with high gas adsorption ability. The introduction of CNF significantly improved the mechanical strength of filters. The composite filter exhibited 94.3% removal efficiency for PM2.5 . Abstract: A biodegradable cellulose-based air filter (Ag-MOFs@CNF@ZIF-8) with multi-layer structure was fabricated by in situ generation of double-component metal-organic frameworks (MOFs) and reinforcement of cellulose nanofiber (CNF). It exhibits good filtration performance, gas adsorption, antibacterial activity and mechanical property. The presence of MOFs could enhance the interaction between the filter and particulate matter (PM) and significantly improve the specific surface area of the composite filter. Thus, the filtration efficiency of the composite filter could reach 94.3% for PM2.5 and the nitrogen adsorption capacity increased to 109 cm 3  g −1 . Furthermore, the Ag-MOFs@CNF@ZIF-8 filter exhibited excellent antibacterial activity against Escherichia coli with an inhibition zone diameter of 18.1 mm. The compressive strength of the composite filter could be up to 501 kPa, approximately 3.8 times higher than that of pure cellulose filter. Herein, this composite filter has a great application potential in PM2.5 removal, toxic gas adsorption and healthcare fields.